Computer-Aided Design of computer system devices - Leonov, Serhii Yuriiovych; Hladkykh, Tetiana Valentynivna (Національний технічний університет "Харківський політехнічний інститут", 2026)
A training manual includes theoretical and practical material related to the provision of computeraided design systems, which is necessary for qualified CAD users in various fields of technology. The basic information on the composition and principles of operation of computer-aided design systems is provided. Methods for modeling the equipment being designed at different stages of computer-aided design are described. For students of the specialty «Computer Engineering» and other technical specialties.
Keywords: training manual; computer system; computer-aided design; mathematical modeling; software model; automated design